Effectiveness of Fiscal Policy Coordination Rules in the Monetary Union - Baran, Bernadeta (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2012)
Stability and Growth Pact is the main rule-based framework for the coordination of national fiscal policies in the economic and monetary union (EMU). It was established to safeguard sound public finances, an important requirement for EMU to function properly. Member states had a lot of determination before setting up a monetary union (nominal criteria were a condition to adopt common currency). In the next years, coordination of fiscal policy was not so successful. In many countries, revenues were temporarily boosted by tax-rich activity, while they didn’t restrict their expenditures. In most countries fiscal policy was pro-cyclical (not anti-cyclical) and they didn’t achieve their MTO. Financial crisis has sharpened budgetary problems in member states and showed the weakness of coordination rules.